2014
DOI: 10.3389/fphys.2014.00454
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of the genomes of a termite and a locust to our understanding of insect neuropeptides and neurohormones

Abstract: The genomes of the migratory locust Locusta migratoria and the termite Zootermopsis nevadensis were mined for the presence of genes encoding neuropeptides, neurohormones, and their G-protein coupled receptors (GPCRs). Both species have retained a larger number of neuropeptide and neuropeptide GPCRs than the better known holometabolous insect species, while other genes that in holometabolous species appear to have a single transcript produce two different precursors in the locust, the termite or both. Thus, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
162
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(168 citation statements)
references
References 180 publications
(257 reference statements)
6
162
0
Order By: Relevance
“…Combination of the whole genome and various transcriptome has improved the sequences of 23 neuropeptide precursor genes reported in a previous prediction (Veenstra, 2014). In fact, the numbers of neuropeptide precursor genes and their products may be even larger because some Locustaspecific neuropeptide genes cannot be identified by homolog searching.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Combination of the whole genome and various transcriptome has improved the sequences of 23 neuropeptide precursor genes reported in a previous prediction (Veenstra, 2014). In fact, the numbers of neuropeptide precursor genes and their products may be even larger because some Locustaspecific neuropeptide genes cannot be identified by homolog searching.…”
Section: Discussionmentioning
confidence: 94%
“…Larger precursors of these signaling messengers are produced mainly in neurons and endocrine cells, after which they are cleaved and modified into mature peptides, then secreted into the extracellular parts (Veenstra, 2000). Alternative splicing often occurs in neuropeptide precursor genes to produce more mature peptides, thereby strongly enhancing neuropeptide diversity (Dircksen et al, 2011;Veenstra, 2014). Mature peptides bind to specific membrane receptors and stimulate intracellular molecules, thus performing their biological functions (Xu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although kinin plays a similar role, this functionality has been lost in Rhodnius prolixus (Bhatt et al, 2014;Te Brugge et al, 2002) while kinin signalling seems to have been lost from the order Coleoptera (Halberg et al, 2015). Although Coast and Schooley (2011) proposed changing the neuropeptide name from DH31 to calcitonin-like diuretic hormone (CT-DH), a new insect neuropeptide family was discovered (Veenstra, 2014) which showed a higher similarity to vertebrate calcitonin and was thus named Calcitonin. To avoid unnecessary confusion, the historical neuropeptide name DH31 (Furuya et al, 2000) would be more appropriate and is therefore used in DINeR.…”
Section: Examples In Use: Insect Dh31 and Kininsmentioning
confidence: 99%
“…This might be advantageous as any pesticide based on 43 it could be relatively selective. The genome sequence of the migratory locust (Wang et al, 2014) 44 showed that the predicted precursor encoding this peptide has all the hallmarks of a classical 45 neuropeptide precursor: a signal peptide and a propeptide encoding multiple copies of the 46 peptide separated by Lys-Arg convertase cleavage sites (Veenstra, 2014 (Fig. 1), while immunoreactive material was completely absent from the central nervous 110 system.…”
mentioning
confidence: 99%